STUDI PEMILIHAN KONTRASEPSI ORAL DI ASRAMA YON ARHANUD 8/MBC DUSUN SERUNI KABUPATEN SIDOARJO PADA BULAN APRIL SAMPAI JUNI 2021 - novia ariani (AFAMEDIS, 2022)
Abstract The Family Planning Program (KB) is one of the Indonesian government's programs, which is held to limit births and reduce population growth and reduce the rate of Indonesia's population. Efforts are being made by the government to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Family planning is one of the strategies to reduce maternal mortality, especially mothers with 4T conditions, namely giving birth too young (under the age of 20), giving birth too often, giving birth too close apart, and giving birth too old (above 35 years old). The design of this research is descriptive. Descriptive research method is a research conducted to describe or describe phenomena that occur in society. This research was carried out at the Yon Arhanud 8/MBC in Seruni, Sidoarjo district from April to June 2021. The tool used in this study was a questionnaire. Based on the results of research conducted by researchers, it can be concluded that from 45 respondents who were examined in the selection of oral contraceptives, 39 people (87%) were using the combined contraceptive pill and 6 (13%) were lactating contraceptive pills. Keywords: Family Planning Program, Family Planning Pills, Seruni Hamlet , Sidoarjo Regency